IDENTIFICATION OF QUALITATIVE AND MORFOMETRIC CHARACTERISTICS OF 4 MONTHS OLD KERINCI DUCKS - B., SUPRIAWAN; ., DEPISON; ., GUSHARIYANTO; ERINA, S. (Majalah Ilmiah Peternakan; Vol 26 No 1 (2023): Vol. 26 No. 1 (2023), 2023)
The purpose of this study was to determine the qualitative and morphometric characteristics of male and female Kerinci ducks aged 4 months. The research material was 72 Kerinci ducks consisting of 36 males and 36 females. The method used is the experimental method. Data on the quantitative characteristics of body sizes were analyzed using the mean difference test (t-test). Main Component Analysis (MCA) was used to identify body size and body shape in male Kerinci ducks and female Kerinci ducks. Data processing used statistical software Minitab version 18. The results showed that there were differences in the qualitative characteristics of male and female Kerinci ducks, namely the color of the head, neck, chest and tail feathers. The body sizes of male Kerinci ducks were significantly different (P<0.05) higher than that of female Kerinci ducks. In conclusion, the qualitative characteristics of male and female Kerinci ducks can be distinguished on the color of neck feathers, chest feathers, tail and head feathers. In male Kerinci ducks, it was found that there was a difference with the minister’s decision, namely the color of the neck feathers. The male Kerinci duck has a higher body size than the female Kerinci duck. Body size markers in male and female Kerinci ducks were chest circumference and body shape markers, namely tibia length in males and femur length in females.